Analisis Pengaruh Penambahan Campuran Enzim Amilase dan Selulase Terhadap Produksi Biogas Dari Limbah Sekam Padi Dengan Metode Solid State Anaerobic Digestion (SS-AD) - Larasati, Dyanung; Hardyanti, Nurandani; Sumiyati, Sri; Nugraha, Winardi Dwi; Syafrudin, Syafrudin (Universitas Diponegoro, 2020)
This research intend to analyze effect of concentrated amylase enzyme and cellulose enzyme, production rate and quality of biogas produced from rice husk waste. The rice husk was given chemical pretreatment by soaking it into NaOH 6 % for 24 hours. Then washed using water so that the pH became normal then dried under the sun before put it inside the reactor with the other enzyme, rumen and urea. The reactor that used has volume of 200ml and has total of 18 reactor with each variable has 2 reactor. Variance of concentrated enzyme that used are 9%, 12%, 15% and 18%. Biogas measurement done every 2 days for 60 days. Result from this research show that addition mixture of amylase enzyme and cellulose enzyme increase yield of biogas that produced. Because yield that produce from reactor with addition of 9%, 12%, 15%, 18% enzyme consecutively are 604 ml, 935 ml, 1041,5 ml and 2922,5 ml. whereas the reactor that not given enzyme only has biogas yield of 115 ml. the highest production rate occur on reactor that were given 18% of enzyme mixture with the production constant rate of 5,39 ml/(grTS day), maximum biogas production amount of 68,53 ml/grTS and the minimum time for biogas to formed is 0,92 days